PENGELOLAAN DAN PERPUTARAN MODAL KERJA PADA UMKM DI UD. WIDYASIH KECAMATAN KUBUTAMBAHAN, KABUPATEN BULELENG - Komang Satya Indriyani Graha; Gst. Ayu ketut Rencana Sari dewi (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to examine about working capital management is based on the" towns" system at UD. Widyasih which is located in Kubutambahan Village, Kubutambahan District, Buleleng Regency. This research was conducted using qualitative methods with primary and secondary data sources. Data obtained from observations, interviews, literature study and documentation. The data analysis techniques used are: 1) data reduction, 2) data presentation, 3) drawing conclusions.The results of this study show that: 1) At UD. Widyasih, which uses more external funds, when presented, internal capital reaches 40% and external capital reaches 60%, which relates to Packing Order Theory, in which this theory uses two sources of internal and external funding. .to help expedite the company's operational system 2) capital structure that includes several criteria, namely asset structure, Growth Opportunity, company size, profitability, and business risk that can affect the sustainability of a company's operations. 3) The application of the cash payment system is carried out to reach customers by providing a predetermined payment period.